Implementation of Merdeka Belajar Kampus Merdeka in the Accounting Study Program Pancha Bhakti University - Risal, Risal; Kristiawati, Endang; Febriati, Febriati; Afif, ali (International Journal of Education, Teaching, and Social Sciences, 2024)
Through the application of MBKM, it is expected that students can optimally achieve learning outcomes, with the free opportunity to take learning credits outside the study program for three semesters. In the effort to implement the MBKM program, preparations are made starting with reviewing the curriculum that adapts to MBKM policies and collaborating with partners. In addition, it also requires readiness from all elements within the Panca Bhakti University environment. The purpose of this research is to see how far the MBKM policy has been implemented, the obstacles encountered in implementing the MBKM policy, as well as the efforts made at the university and faculty levels to support the implementation of the MBKM policy in the Panca Bhakti University Accounting Study Program. The method used in this research is a survey method. The results of the research show very positive things, where lecturers, education staff and students have supported the implementation of the MBKM policy in the Accounting Study Program and it is hoped that the results of this research can become recommendations in strengthening the application of MKBM at the faculty and university levels.